Pillow Smasher ( Penggebuk Bantal ) Eksplorasi bunyi dan pukulan Penciptaan Musik Ekspresimental Bunyi - Nurpebia, Vera; Setiaji, Deden (Jurnal Ilmu Sosial, Humaniora dan Seni, 2025)
Pillow Smasher is an experimental performance art exploration that combines sound, body movement, and everyday objects, especially pillows, as a medium for emotional expression. Departing from the need for a cathartic space, especially among teenagers and students facing psychological stress, this work utilizes the act of hitting a pillow as a symbol of releasing pent-up feelings. With a performative approach and unconventional sound aesthetics, Pillow Smasher displays emotional dynamics through rhythm, beats, and spontaneous movements. This work is not only artistic, but also educational and therapeutic, and serves as an alternative art learning that is inclusive, reflective, and based on personal experience. This project emphasizes that art can be a powerful medium for expressing emotions, reflecting inner states, and creating a space for honest and safe expression.